Efforts to Improve the Disciplinary Character Students of SMAN 1 Kandis Ogan Ilir - Yanti, Meri (EDUCATE : Journal of Education and Culture, 2023)
The disciplinary character of students can grow well if it is based on the individual's willingness to do good habituation and go through a long and continuous process that involves the role of the family, educational institutions and social environment. This study limits the formulation of the problem to: 1) How are efforts to improve the disciplinary character of students of State High School 01 Kandis Ogan Ilir, 2). What are the supporting and inhibiting factors for efforts to improve the character of students of State High School 01 Kandis Ogan Ilir?. This research is a Qualitative research. The data collection technique of this study uses the method of observation, documentation, interviews. Data analysis techniques used include: Data analysis in qualitative research, carried out at the time of data collection, and after completion of data collection in a certain period. At the time of the interview, the researcher had already conducted an analysis of the answers of the interviewee. If the answers interviewed after dialysis feel unsatisfactory, then the researcher will continue the question again, to a certain degree, obtained data that is considered credible. The results of the study explained that: 1). Discipline from the beginning has been instilled in all school residents at State High School 01 Kandis Ogan Ilir, be it among students, educators or other educational personnel using teaching and learning methods